Operational Risk Assessment for the Pollination Service with Apis mellifera Bees in Cashew Crops in Vichada, Colombia - Castro Mercado, Lizeth; Bravo Bastidas, Juan José; Osorio Gómez, Juan Carlos (International Journal of Forestry Research, 2024)
The cashew tree relies heavily on the presence of pollinators during the peak receptivity of its flower to facilitate the transfer of pollen from the stamen to the stigma and ensure successful fruit production. Apis mellifera bees play a crucial role as intermediaries in the pollination process of the fruit, simultaneously extracting nectar and pollen from the flowers. The pollination service (PS) is susceptible to various risk factors that, if realized, could impact both the beekeeping industry and cashew production. This article aims to assess the operational risks associated with pollination service for Anacardium occidentale production in Vichada, Colombia, as a strategic measure to safeguard the business’s value. Drawing on expert opinions and relevant literature, nineteen risks were identified, encompassing threats such as fires, thefts, attacks by wild animals, unexpected rains, etc. Following the application of Failure Mode and Effects Analysis (FMEA), four risks were prioritized based on their severity and occurrence. Subsequently, Value at Risk (VaR) was employed for risk evaluation. The anticipated loss for the pollination service, resulting from these prioritized risks: 1, 9, 12 and 13, was quantified at $226674 ± $19096 per year for an 8000-hectare margin with a confidence level of 95%. The economic loss for 16000 hectares was $453348 ± $38192. This substantial value is of great significance to the beekeeping sector, translating to a loss of $27.3 per hectare per year and directly impacting the estimated $437824 loss in the cashew sector. Such losses have far-reaching consequences, affecting the livelihoods of peasant beekeepers in the region and potentially discouraging the maintenance of bee colonies and forests.